Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 35833 by abdo mathsup 649 cc last updated on 24/May/18

fond lim_(n→+∞)   n^a   {ln(1+e^(−n) ) −e^(−n) } with a>0

fondlimn+na{ln(1+en)en}witha>0

Commented byprof Abdo imad last updated on 25/May/18

we have for ∣x∣<1  ln^′ (1+x) =(1/(1+x)) =Σ_(n=0) ^∞ (−1)^n x^n   ⇒ ln(1+x) =Σ_(n=0) ^∞  (((−1)^n x^(n+1) )/(n+1)) =Σ_(n=1) ^∞  (((−1)^(n−1)  x^n )/n)  so  ln(1+x) = x  −(x^2 /2) +o(x^3 )(x→0)⇒  ln(1 +e^(−n) ) = e^(−n)  − (e^(−2n) /2)  +o(e^(−3n) )(n→+∞)  n^a { ln(1+e^(−n) )−e^(−n) } ∼ −(1/2)n^a  e^(−2n)  (n→+∞)  but lim_(n→+∞)  n^a  e^(−2n)  =lim_(n→+∞) e^(aln(n)−2n)   =lim_(n→+∞)   e^(n{ a((ln(n))/n) −2})  = lim_(n→+∞)  e^(−2n)  =0 so  for all a>0 lim_(n→+∞) n^a {ln(1+e^(−n) ) −e^(−n) } =0

wehaveforx∣<1ln(1+x)=11+x=n=0(1)nxn ln(1+x)=n=0(1)nxn+1n+1=n=1(1)n1xnn soln(1+x)=xx22+o(x3)(x0) ln(1+en)=ene2n2+o(e3n)(n+) na{ln(1+en)en}12nae2n(n+) butlimn+nae2n=limn+ealn(n)2n =limn+en{aln(n)n2}=limn+e2n=0so foralla>0limn+na{ln(1+en)en}=0

Answered by tanmay.chaudhury50@gmail.com last updated on 24/May/18

when n→∞  then e^(−n) →0  so given limit (∞×0) form  =((lim)/(n→∞))(({ln(1+e^(−n) )−e^(−n) })/(1/n^a )) ((0/0)) form  using lhospitsl  =((lim)/(n→∞))×(({(1/((1+e^(−n) )))×e^(−n) ×−1}−{e^(−n) ×(−1)})/(−a×n^(−a−1) ))  =((lim)/(n→∞))×(({((−e^(−n) )/(1+e^(−n)  ))}+e^(−n) )/(−a×n^(−a−1) ))  =((lim)/(n→∞))×(({−e^(−n) +e^(−n) +e^(−2n) )/((1+e^(−n) )×(−a×n^(−a−1) )))  =(((−1)/a))×((lim)/(n→∞))(e^(−2n) /(1+e^(−n) ))×n^(a+1)   =(((−1)/a))×((lim)/(n→∞))(1/(e^(2n) +e^n  ))×n^(a+1)   =(((−1)/a))×((lim)/(n→∞))(1/(e^n +1))×(n^(a+1) /e^n )  =((−/a))×((lim)/(n→∞))×((1/(e^(2n) +e^n ))/(1/n^(a+1) ))  contd

whennthenen0 sogivenlimit(×0)form =limn{ln(1+en)en}1na(00)form usinglhospitsl =limn×{1(1+en)×en×1}{en×(1)}a×na1 =limn×{en1+en}+ena×na1 =limn×{en+en+e2n(1+en)×(a×na1) =(1a)×limne2n1+en×na+1 =(1a)×limn1e2n+en×na+1 =(1a)×limn1en+1×na+1en =(a)×limn×1e2n+en1na+1 contd

Terms of Service

Privacy Policy

Contact: info@tinkutara.com